Proposition of a collaborative platform for virtual design studios. (8th March 2010) - Bouarfa, Hafida; Toubaline, Nesrine
A virtual design studio is distributed across space and time and information is represented electronically. The technology available for the studios includes Computer Aided Design (CAD), image processing, World Wide Web, video conferencing, e-mail, shared files and files transfer. The potential for this technology in a design necessary. However, environment is to reduce the need to physically meet when collaboration is sophisticated technological tools do not warrant a successful collaborative design work. The importance of humans in the process is fundamental. That is why we introduce the concept of leader agent or coordinator. The objective of this paper is to propose a collaborative platform for virtual design studios.